Associations between physical activity and proactive control and the modulating role of working memory. (May 2023) - Ren, Tian; Ye, Xuejian; Li, Zheng; Li, Qingyi; Zhang, Xinyuan; Dou, Wenjie; Jia, Xi; Li, Bao-ming; Wang, Chunjie
Abstract: Accumulating evidence indicates positive associations between physical activity (PA) and cognitive control. Proactive control, the ability to maintain goal-relevant information in preparation of upcoming task demands, is a critical component of cognitive control. However, little research has examined the association between PA and proactive control. To address this issue, a total of 132 university students were recruited and divided into two groups based on reported regular PA during past week. All participants completed two common cognitive control tasks: the AX Continuous Performance Task (AX-CPT) and the Cued Task-Switching Paradigm (CTS). In comparison with the low PA group, the high PA group showed greater proactive control efficiency on both tasks. Moreover, proactive control indices significantly correlated between the two tasks for the high but not for the low PA group. Further, working memory significantly modulated the association between PA and proactive control efficiency of CTS. Although the present cross-section design does not allow us to test the causal relationship between PA and proactive control, these findings may have important implications for developing effective intervention strategies which aim to promote proactive control through increasing PA or to promote PA through increasing proactive control. Moreover, individual differences in working memory are important to consider when we aim to design such interventions. Highlights: Proactive control engagement was better in young adults with more physical activity. Consistency in proactive control across tasks was higher in young adults with more physical activity. Working memory may play an important role in the association between physical activity and proactive control.